Pathogencity, yield loss assessment and management of root -knot nematode, meloidogyne incognita (kofoid and white) chitwood on chilli (capsicum annum L.) - Rajitha R (Department of Agricultural Entomology, College of Agriculture, 2003)
A study was conducted in pots to determine the pathogenicity of the root-knot nematode, Meloidogyne incognita (Kofoid and White, 1919) Chitwood, 1949 on chilli (Capsicum annuum L.). A significant reduction was seen in the growth parameters' at 30, 60 DAT and final harvest when chilli plants were inoculated with 50, 100, 200 and 300 hllOO g soil. A progressive reduction in yield was also observed wi th increase in the inoculum levels, the reduction in yield ranging from 17.59 to 62.99 per cent. Multiplication of the nematode was high at 50 and 100 hll 00 g soil. Considering the importance of the crop in the state, 40 per cent loss in .- yield and multiplication of the nematode in relation to its initial density at 100 Jz 11 00 g soil, the damage threshold of the nematode was fixed as 100 lj100 g soil. Thirteen accessions including high yielding varieties and local accessions were screened in pots for resistance to M. inco gnita. Pusa Sadabahar and Khandari were moderately resistant to the nematode. Pusa Sadabahar,Pusa Jwala and Pant C-l were moderately resistant to infestation of chilli thrips, Scirtothr ips dorsalis and chilli mite, Polyphagotarsonemus latus. The high yielding varieties, Jwalamukhi and Jwalasakhi released by Kerala Agricultural University were susceptible to , the nematode but moderately resistant to pest infestation. Three bioagents viz., AMF @ 250 spores per plant, fluorescent pseudomonads 2 per cent and Trichoderma sp. 5 per cent and oilcakes viz., neem cake and mustard cake @ 1 t ha-l were evaluated for their efficacy in controlling M. incognita in comparison with carbofuran @l kg ai ha-l in pots. Treatment with the bioagents protected chilli plants better from the infestation of the nematode while amendment of soil with oilcakes resulted in better growth of plants. Yield was also higher in plants treated with bioagents. Among the bioagents, application of AMF @ 250 spores